La maternité célibataire au Maroc : pour une approche dynamique de l’expérience - Amal Bousbaa (L’Année du Maghreb)
Single motherhood in Morocco often refers to a difficult experience marked by social exclusion. Indeed, pre-established legal, religious and social norms prohibit sexuality and reproduction outside of marriage. In a context marked by social control of reproduction and the repression of transgressive sexualities, particularly sexual relations outside of marriage, single mothers find themselves alone to take care for a child born out of wedlock, and to face an experience marked by social stigmatization and precariousness. The aim of this article is to understand how single mothers act in the face of an excluding social environment. How do they manage to adapt and reorganize their lives around the experience of single motherhood? What are the strategies and resources deployed to achieve this? The hypothesis put forward here consists in assuming that single mothers do not go through the path of exclusion without showing resistance and an ability to reorganize their new life. Based on a qualitative survey conducted as part of a doctoral thesis in Sociology, the analysis aims to account for the adaptations of single mothers and the strategies put in place to deal with the repercussions of stigma in everyday social interactions.